The idealPosition System: Sebagai Solusi Pendukung Keputusan untuk Menentukan Pemain Bola yang Ideal Berdasarkan Posisi Pemain - Faisal F Taran; Abdul Mubarak; Firman Tempola; Achmad Fuad; Salkin Lutfi (JUSIFO : Jurnal Sistem Informasi, 2020)
In North Maluku, especially in Ternate, many football schools have been opened to train and find potential Indonesian National players. One of them has contributed to producing Indonesian National player candidates, namely Sekolah Sepak Bola (SSB) Tunas Gamalama. The problems that occur at this time at SSB Tunas Gamalama, managers and coaches are difficult to determine the ideal player to fill each position. Oftentimes, SSB Tunas Gamalama students choose a position according to their idol football players, and also because of the popularity of these positions. The tendency of SSB Tunas Gamalama students to be like this results in an imbalance of potential players in certain position. During this time the coach takes a long time and is often subjective in selecting players at every position available. In this research, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method was used as a method of decision support. This article aims to build a Decision Support System (DSS) in determining the ideal football player based on the player's position (The idealPosition System) using the TOPSIS method. This research produces DSS which can be used to determine the ideal soccer player based on the player's position.